Understanding the shift of correlation matrices during financial crisis: A network topology - Yusoff, Nur Syahidah; Sharif, Shamshuritawati (2015)
Understanding the shift of correlation matrices in any process is not an easy task.From the literatures, the most popular and widely used test for correlation shift is Jennrich's test.This motivates us to use it in this paper.However, if after hypothesis testing the hypothesis of stable process correlation is rejected, then the next problem is to find out the root causes of that situation.In this paper, network topology approach will be used to understand the shift.A case study will be discussed and presented to illustrate the advantage of this approach.